Quality Assurance of Nonformal Education Financing - Rohaeni, Yeni; Prasetyo, Iis; Puspita, Mareta (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This study aims to describe the implementation of financing quality assurance at the Community Learning Activity Center (PKBM) in South Solok Regency. Through an exploratory qualitative approach, the research was conducted in three PKBMs with different regions. The results show that the implementation of financing quality assurance is quite good in the aspects of implementation and evaluation, but still needs improvement in the aspects of planning and follow-up development. The benefits of the implementation of financing quality assurance are seen in the improvement of service quality, the effectiveness of the use of funds, and the positive impact on the surrounding community. The main obstacle faced is the limited sources of financing that cause dependence on government assistance.